THE EFFECT OF WORK-LIFE QUALITY AND EMPLOYEE EMPOWERMENT ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR, WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE - Mochammad Ivan Falah; Ahyar Yuniawan (SOSIOEDUKASI, 2026)
A corporation can achieve growth by focusing on employee responsibilities due to the evolution in the spheres of commerce and technology within globalization’s Industry 4.0. Employees are expected to enhance their competencies within organizational contexts. An organization thrives when its members exceed ordinary duties delivering performance far beyond expectations. The present research aims to explore the effects of Quality of Work Life (QWL) and Workplace Empowerment on Organizational Citizenship Behavior (OCB), with Organizational Commitment serving as a mediating construct in the hypothesized model. This investigation was undertaken encompassing the entirety of personnel at PT. Nuswantoro Manunggal Jati, totaling 85 individuals. This research is situated within a quantitative framework and deploys Partial Least Squares Structural Equation Modeling (PLS-SEM) for data analysis. The results establish that Quality of Work Life (QWL) and Workplace Empowerment contribute positively and significantly to Organizational Commitment, which then exerts a favorable effect on OCB. Furthermore, Organizational Commitment is confirmed to function as a mediating variable that potentiates the impact of QWL and Workplace Empowerment upon OCB. The study illuminates the critical role of Organizational Commitment as a conduit through which the quality of the work environment and empowerment practices translate into Organizational Citizenship Behavior, carrying meaningful implications for the advancement of human resource management and the enhancement of broader organizational performance.